"M*A*S*H" - Averback, Hy, 1920-1997.; Alda, Alan. (USA 20th Century Fox Television, 1972)
The 4077th Mobile Army Surgical Hospital is stuck in the middle of the Korean war. With little help from the circumstances they find themselves in, they are forced to make their own fun. Fond of practical jokes and revenge, the doctors, nurses, administrators, and soldiers often find ways of making wartime life bearable. Nevertheless, the war goes on
From June 25, 1950 to July 27, 1953, America waged war with Korea. To tend to the wounded, the government sent the Mobile Army Surgical Hospital to the front lines to nurse the soldiers. In the camp called the 4077th, Captain Benjamin Franklin "Hawkeye" Pierce witnesses this ferocious yet pointless fight go on while trying to keep the mood light with wise-cracking and practical jokes. He meets many illustrious people, such as the near-psychic company clerk Corporal Walter "Radar" O'Reilly, the short-tempered Head Nurse Major Margaret "Hot Lips" Houlihan, Maxwell Q. Klinger who will do anything to be sent home, stern Colonel Henry Blake, the neurotic Major Frank Burns (Hawkeye's roommate), likeable Father Francis Mulcahy, countless other doctors and nurses, and Hawkeye's best friend, fellow fun-loving prankster Captain "Trapper" John McIntyre. During the war, Hawkeye sees many changes occur around him: Trapper, Frank and Radar are sent home, Klinger takes over as company clerk, B.J. Hunnicutt becomes Hawkeye's new best friend and plays around with him instead, arrogant but educated Charles Emerson Winchester III becomes Hawkeye's new roommate, and Blake's plane is shot down over the Sea of Japan, spinning in and killing him. He is replaced by Colonel Sherman Potter, an experienced man who becomes a father figure, albeit a strict one, to the group. Countless doctors and nurses appear throughout, and you can always count on the insane Colonel Samuel Flagg to try to screw everything up.
Keywords: Comedy -- American Corner; Drama; War